New Discovery of Oligocene Strata in the Topernawi Formation, Turkana County, Kenya - Sousa, Francis J.; Cox, Stephen E.; Hemming, Sidney R.; Rasbury, E. Troy; Steponaitis, Elena; Hatton, Kevin; Saslaw, Mae; Henkes, Gregory; Princehouse, Patricia; Vitek, Natasha S.; Nengo, Isaiah (Frontiers in Earth Science, 2022)
New field observations and 40Ar/39Ar geochronology reveal that the Topernawi Formation of the Ekitale Basin, northern Turkana Depression, Turkana County, Kenya was deposited entirely during the Oligocene between 29.7 ± 0.5 Ma and 29.24 ± 0.08 Ma. These bracketing ages are determined via new 40Ar/39Ar geochronology on a basaltic lava flow at the base of the section and a felsic ignimbrite near the top. A newly discovered basal unit and interbedded lava flow result in a new total sedimentary thickness of 92 meters. The Topernawi Formation is the oldest dated syn-rift sedimentary section in the northern Turkana Depression.